Philosophical inquiry in the Malaysian educational system –reality or fantasy? - Preece, Abdul Shakour Duncan; Juperi, Juhasni Adila (2014)
Thinking skills are a popular topic of conversation nowadays among Malaysian educationists. These experts lament that Malaysian students are ill-equipped to face the challenges of life in the 21st Century. As a solution to this and other problems, a reform document was proposed by the Malaysian Ministry of Education (MOE) in 2012. The 'Malaysian educational blueprint' as it is called, has at last recognized the importance of critical thinking skills and seeks ways to include these into the national curriculum. Philosophy for Children (P4C) is a teaching method that develops critical thinking and analytical reasoning in children. The paper therefore recommends the use of P4C to achieve the goals of the Malaysian educational blueprint vis-à-vis critical thinking, since it has proven its effectiveness in various studies around the world. The main purpose of this paper, therefore, is to raise the following pertinent questions: how suitable is P4C for the Malaysian education system? Secondly, how will P4C be implemented, bearing in mind the challenges within the unique Malaysian context? These questions and others, need to be explored if P4C is to be implemented successfully, and Malaysia is to be transformed into a more 'thinking nation' through education.